Energy assessment of a plug-in hybrid vehicle propulsion management system - Campino, Miguel (2020)
Plug-In hybrid vehicles have a complex propulsion system management, trying to manage the conventional and electric motorization in the most energy efficient way according to the driving dynamics, topography and battery charge state. In this sense, the aim of this work is to analyze the energy performance of plug-in hybrid vehicles, based on road tests, under real conditions of use, focusing on the management system of the two energy sources present, varying the level of battery charge at the start of the test to visualize the impact of this change. To complement the analysis and in order to better understand the operation of the management system, a methodology for applying the VSP parameter is used, which allows the load state to be approximated according to the vehicle’s operating mode, alternating between the three modes according to the conditions at the time in question, prioritizing the electric motor when the state of charge of the battery is maximum. These results confirm the fact that plug-in hybrid vehicles allow better electricity management due to the diversity of external or internal charging sources, which makes this type of vehicle more efficient and versatile than conventional hybrids, allowing a reduction in fossil fuel consumption and consequently a reduction in the emission of pollutant gases, making this type of vehicle a very competitive alternative in the transport sector in view of the current challenges due to the goals present in the current European regulations.